Vegetation Richness of the Igarapé da Fortaleza Hydrographic Basin, AP-010, Amapá, Brazil (Research, Society and Development, 2021)
The objective of this research is to know the diversity of plant species collected in the scope of the Igarapé da Fortaleza Hydrographic Basin, between the municipalities of Santana and Macapá, State of Amapá. From the organization of digital data records of species collected and registered in national and international herbaria, the records collected in the State of Amapá were extracted, comprising the scope of the research interest area. The floristic composition was evaluated by the richness of individuals distributed in genera and species. The families were organized according to the APG IV and the nomenclature update and verification of life habits were carried out by consulting the Flora do Brasil 2020 and Tropicos websites. A total of 501 samples were registered in 18 herbariums, 11 of which were national and seven internationals, of which 235 were deposited in the Herbarium Amapaense. 245 species belonging to 60 families and 169 genera were recorded. Fabaceae was the family with the largest number of species recorded, followed by Poaceae and Orchidaceae, and the most frequent habit was herbaceous. It is concluded that the floristic diversity of the Igarapé da Fortaleza Hydrographic Basin is quite significant, but even with the expressive diversity recorded, there is still a need for additional studies to expand the knowledge of the existing diversity.